The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/19420670903442053
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Social Enterprise and Social Entrepreneurship in Europe and the United States: Convergences and Divergences

Abstract: The concepts of social enterprise and social entrepreneurship are making amazing breakthroughs in EU countries and the United States. Until recently, the debates on both sides of the Atlantic have taken place in parallel trajectories with few connections among them. In the first part of the paper, we describe the European and US historical landscapes in which those concepts took root. In the second part, we analyse how the various conceptualizations have evolved. This analysis paves the way for the third part,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
653
0
126

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 941 publications
(832 citation statements)
references
References 18 publications
9
653
0
126
Order By: Relevance
“…The importance of terminology would be to decrease the boundaries between sectors "socioenvironmental businesses" and "socioenvironmental entreprenership" have also been used to emphasize the need to incorporate the environmental dimension to solutions proposed by this type of business (Defourny & Nyssens, 2010;Fischer & Comini, 2012;Haigh & Hoffman, 2012. Improving living conditions, according to scholars such as Prahalad and Hart (2002), takes place through the granting of access to any goods and services that were previously available only to privileged upper strata.…”
Section: Social Business: Hybridism Rationale and Management Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of terminology would be to decrease the boundaries between sectors "socioenvironmental businesses" and "socioenvironmental entreprenership" have also been used to emphasize the need to incorporate the environmental dimension to solutions proposed by this type of business (Defourny & Nyssens, 2010;Fischer & Comini, 2012;Haigh & Hoffman, 2012. Improving living conditions, according to scholars such as Prahalad and Hart (2002), takes place through the granting of access to any goods and services that were previously available only to privileged upper strata.…”
Section: Social Business: Hybridism Rationale and Management Modelmentioning
confidence: 99%
“…Much of the existing literature falls into one of three main lines of investigation of social businesses (Young, 2007): the European perspective, born from the Social Economy tradition (associations and cooperatives), strongly encourages businesses to carry out public duties; the North American view sees social businesses as businesses that use market logic to try to solve social problems; a third current, proposed by researchers from emerging countries, emphasizes business initiatives aimed at reducing poverty and transforming the social conditions of marginalized individuals. (Comini & Teodósio, 2012;Defourny & Nyssens, 2010;Kerlin, 2006Kerlin, , 2013Young & Lecy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this article contributes to the ongoing discussion on the theoretical conceptualization of both cooperatives and social enterprises (Borzaga and Tortia 2006;Defourny and Nyssens 2010;Kerlin 2006;Poledrini 2015;Valentinov 2013;Young and Lecy 2014). Previous work has shown that neo-institutional economic theory, although widely applied in nonprofit studies, can neither adequately explain the existence of traditional, nor third-party-focused cooperatives as a type of social enterprise (Borzaga and Defourny 2001;Laville and Nyssens 2001;Dart 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A social enterprise is a market-oriented economic activity that serves a social goal, although, as Defourny and Nyssens (2010) pointed out, the definition of a social enterprise varies between countries. Social enterprises are generally defined as businesses that have social aims, such as local employment; are usually based on a commitment to build local capacity; and are answerable to their members for their social and economic effect.…”
Section: Indigenous Communities Buy Hotelsmentioning
confidence: 99%
“…In Australia and overseas, enterprises such as these have discovered that identifying and promoting themselves as being owned by the Indigenous community can be an effective marketing technique. The Crossing Inn is not a community-owned hotel in the 'classic' Gothenburg sense, nor is it a social enterprise of the kind discussed by researchers such as Defourny and Nyssens (2010). A social enterprise is generally understood as a market-oriented economic activity that serves a social goal.…”
Section: Abandoning the Ideals Of A Social Enterprisementioning
confidence: 99%